Unriddling Academic Dishonesty through the Lens of Teacher and Student Perceptions - Muhammad Saleem; Gulnaz Akram; Areeha Khan Durrani; Ali Raza Siddique (NUST Journal of Social Sciences and Humanities)
This study sought to explore contributory factors of academic dishonesty. Academic dishonesty is being practiced yet little research has been conducted on the subject. Subsequently, this study employed the qualitative approach for in-depth exploration of the factors of academic dishonesty. In this study, focus group discussions were conducted with two groups of participants; university students (N=12) and university teachers (N=08) of The Islamia University of Bahawalpur, Pakistan. Participants for this study were recruited through purposive sampling. Three research questions were asked to the participants: Q1) How is academic dishonesty described by students and teachers? Q2) What would be the possible types of academic dishonesty? and Q3) What are the pros and cons of academic dishonesty in the long run? Their responses were audio taped and the collected data were transcribed by following transcription steps provided by Humble (2015). For data analysis, NVivo (12) was utilized and factors were extracted. The prudent findings found that cheating, plagiarism, falsification and failure of system are identified as the most prominent factors. The findings of this study concluded that these factors significantly shape-up academic dishonesty in higher learning institutions. Findings of this study would help educationists to bring about reforms in the educational sector.